ANTARA BENCI DAN RINDU: HUBUNGAN INDONESIA-MALAYSIA DAN ISU TENAGA KERJA ILEGAL DI MALAYSIA - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2012)
The objective of this research is to get adeguate explanation and understanding to Indonesia-Malaysia relation in related to solving problem of the illegal workers. The method was using descriptive and qualitative. This study shows, that illegal workers was a serious problem which give impact to the Indonesia-Malaysia relations. In Malaysia contexs, its can be impact to the economy, social, security and etc. Nevertheless, Indonesian government must be take integrative and comprehensive program through good recruitment, regulation, advocation and administrative services.